KINETIC ISOTOPIC FRACTIONATION DURING DIFFUSION OF IONIC SPECIES IN WATER - Richter F.M.; Mendybaev R.A.; Christensen J.N.; Hutcheon I.D.; Williams R.W.; Sturchio N.C.; Beloso Jr.A.D. (My University, 2006)
Experiments specifically designed to measure the ratio of the diffusivities of ions dissolved in water were used to determine DLi/DK, D7Li/D6Li, D25Mg/D24Mg, D26Mg/D25Mg, and D37Cl/D35Cl. The measured ratio of the diffusion coefficients for Li and K in water (DLi/ DK = 0.6) is in good agreement with published data, providing evidence that the experimental design being used resolves the relative mobility of ions with adequate precision to also be used for determining the fractionation of isotopes by diffusion in water. In the case of Li, we found measurable isotopic fractionation associated with the diffusion of dissolved LiCl (D7Li/D6Li = 0.99772 ? 0.00026). This difference in the diffusion coefficient of 7Li compared to 6Li is significantly less than that reported in an earlier study, a difference we attribute to the fact that in the earlier study Li diffused through a membrane separating the water reservoirs. Our experiments involving Mg diffusing in water found no measurable isotopic fractionation (D25Mg/D24Mg = 1.00003 ? 0.00006). Cl isotopes were fractionated during diffusion in water (D37Cl/D35Cl = 0.99857 ? 0.00080) whether or not the co-diffuser (Li or Mg) was isotopically fractionated. The isotopic fractionation associated with the diffusion of ions in water is much smaller than values we found previously for the isotopic fractionation of Li and Ca isotopes by diffusion in molten silicate liquids. A major distinction between water and silicate liquids is that water surrounds dissolved ions with hydration shells, which very likely play an important but still poorly understood role in limiting the isotopic fractionation associated with diffusion. ? 2005 Elsevier Inc. All rights reserved.
Keywords: ISOTOPIC FRACTIONATION; SILICATE MELT